DEVELOPING A STRATEGIC SHARED VALUE APPROACH FOR CSR PROGRAMS AT PT BUKIT ASAM TBK - Titin Dwi Oktariani; Melia Famiola (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
PT Bukit Asam Tbk (PTBA) is undergoing an important strategic transition driven by rising global sustainability expectations, national energy transition commitments, and evolving socio-economic conditions in the communities surrounding its operationsThis study develops a Strategic Shared Value Approach for PTBA’s CSR programs through qualitative strategic analysis supported by a structured prioritization method. The research begins with an assessment of PTBA’s socio-economic and environmental operating context using Porter’s Diamond Model. This analysis identifies several regional advantages, including post-mining land availability, emerging livelihood potential, community capabilities, and established multi-stakeholder networks. These contextual strengths reveal opportunities for PTBA to design shared value initiatives that enhance livelihood diversification, promote sustainable land use, and strengthen community adaptability in the context of regional transitions. To identify the shared value pathway that best aligns with PTBA’s strategic aspirations, the research incorporates the Analytical Hierarchy Process as a structured decision-support tool. Within the qualitative scope of this study, the method is used to systematically organize reasoning and compare alternatives based on strategic alignment, stakeholder expectations, feasibility, and potential for sustained impact. This approach provides a clear rationale for selecting a priority pathway without introducing operational or quantitative complexity. The assessment results in the identification of one pathway with the strongest relevance to PTBA’s future direction. this study demonstrates PTBA’s potential to transition from traditional CSR practices toward meaningful shared value creation by leveraging regional strengths, organizational capabilities, and its sustainability commitments.